Brainstem Glioma in Adults - Hu, Jethro; Western, Stephen; Kesari, Santosh (Frontiers in Oncology, 2016)
Brainstem gliomas are not nearly as common in adults as they are in children. They are likely the final common consequence not of a single disease process but of several. They can be difficult to diagnose, and are challenging to treat. Clinical studies of this diagnosis are few and generally small. Because of these factors, our understanding of the biology of adult brainstem glioma is incomplete. However, the knowledge base is growing and progress is being made. In this article, we will review the current state of knowledge for brainstem glioma in adults, and identify key areas for which additional information is required..